Study on visible–IR radiative properties of personal protective clothings for firefighting. (January 2015) - Collin, A.; Marchand, A.; Kadi, A.; Acem, Z.; Boulet, P.; Pageaux, J.; Pinson, S.; Lepelletier, M.; Van Waelfelghem, Y.; Magnolini, F.; Charette, H.
Abstract: This work deals with the radiative properties of personal protective clothings worn during firefighting operations by firemen. Several intervention jackets are tested coming from different Fire and Rescue Services in France. The present study focuses on the spectral absorptivity of these equipments over visible–IR domains. The spectral absorptivity in the IR range is mainly responsible for the conversion of radiative transfer coming from the flame into heat flux through the protective jacket. This work shows that the mean absorptivities of different equipments are high, close to 90%, which penalizes the thermal protection. This study demonstrates that the colored textile has a weak effect on the radiative properties and then on the thermal protection. On the contrary, the dyeing mode can decrease the absorptivity, hence improving the thermal protection of jackets, a dyed jacket being more efficient in the present test than a jacket made of fibers dyed before weaving. Finally, this paper presents mean absorptivities based on Planck's averages for reference temperatures between 800 K and 1400 K, allowing to compare different personal protective clothings. Abstract : Highlights: Spectroscopy analysis and measurements. Radiative properties of fire intervention jackets. Color and dyeing effects on the radiative properties of PPE.